PENGARUH MODEL KOOPERATIF TIPE NHT BERBANTUAN PRAKTIKUM TERHADAP HASIL BELAJAR SISWA PADA MATERI PEMISAHAN CAMPURAN - Subekti, Abong; Enawaty, Eny; Lestari, Ira (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2018)
Abstract: This research was conducted to find out is there any differences in learning outcomes and how great the students’ influence taught using cooperative learning model of Numbered Heads Together (NHT) type aided by practicum in separation material of grade VII students of SMPN 4 Satap Belimbing Hulu. The type of research applied to this research was Quasy Experimental Design with Nonequivalent Control Group Design as the research design. The population used in collecting the data in this research was from all class of VII at SMP Negeri 4 Satap Belimbing Hulu, they were VIIA and VIIB. The sampling technique used is the sample saturated with class VIIA as experiment class and class VIIB as control class. The tools of data collecting used were the test learning outcomes. The results of the study showed that the learning outcomes of the experiment class with the control class with value sig. 0,001 < 0,05 meant there were differences between learning outcomes from the control class that used conventional learning and the experiment class that used cooperative learning model of Numbered Heads Together (NHT) type aided by practicum. cooperative learning model of Numbered Heads Together (NHT) type aided by practicum influenced about 38.3% with effect size 1.19 included in high category against the learning outcomes in separation material toward students of class VII at SMP Negeri 4 Satap Belimbing Hulu.Keywords: Numbered heads together (NHT), mixed separation, learning                 outcomes.